2020
DOI: 10.1088/1742-6596/1668/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Activation measurement of a-induced cross sections for 197Au: analysis in the statistical model and beyond

Abstract: Cross sections of ( α,γ), (α,n), and (α,2n) reactions for 197Au were measured below the Coulomb barrier using the activation technique. The new data are analyzed in the statistical model and in a simple barrier transmission model. Sensitivities of the resulting cross sections on the underlying parameters are discussed. It is found that the cross sections in the statistical model depend sensitively on the tail of the imaginary α-nucleus potential at large radii outside the colliding nuclei. Contrary, the cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Furthermore, we modified TALYS to implement the recent ATOMKI-V1 potential [22]. It was found that the total reaction cross section of α + 197 Au from the different AOMPs varies by less than a factor of two at higher energies of 25 MeV above the Coulomb barrier; however, around 10 MeV, i.e., in the center of the Gamow window at T 9 ≈ 2.5, the predicted cross sections vary dramatically by about four orders of magnitude [23]. Obviously, the reason for the wide range of predictions should be understood.…”
mentioning
confidence: 99%
“…Furthermore, we modified TALYS to implement the recent ATOMKI-V1 potential [22]. It was found that the total reaction cross section of α + 197 Au from the different AOMPs varies by less than a factor of two at higher energies of 25 MeV above the Coulomb barrier; however, around 10 MeV, i.e., in the center of the Gamow window at T 9 ≈ 2.5, the predicted cross sections vary dramatically by about four orders of magnitude [23]. Obviously, the reason for the wide range of predictions should be understood.…”
mentioning
confidence: 99%